Factors Influencing the Application of Regional Management Information System-Regional Owned Agency in the Kolaka District Health Service - Sari Irianto, Novita; Saafi , La Ode; Munir, Sanihu (Magister Kesehatan Universitas Mandala Waluya, 2025)
Introduction: Along with the rapid development of information technology, there is also the development of an increasingly sophisticated accounting information system in the world of health care, without exception in terms of goods management. Therefore, the management of information systems is an activity that must be carried out in order to ensure that an application of the information system used by the Government agencies as a tool of goods management can provide adequate guarantees of control. Method: The data used is statistical testing using Warp PLS software to find out the factors which affect the implementation of the information system of regional management - goods owned by the District of Kolaka District. Result: The study was conducted in the Kolaka district health department in southeastern Sulawesi province from March to June 2024. The population in this study was an officer who worked in the management of local property in the Kolaka district health department so they obtained a sample of 54 people. Conclusion: The conclusion in this journal is that Planning, Procurement, Use, Entrepreneurship, Exploitation, Maintenance and Elimination influence the Quality of Management of Local Property. It is recommended that each instance's asset manager be included in order to improve their skills in operating Regional Management Information System - Regional Owned Agency applications and to be able to compile a room inventory card at each of those instances.